Instructional Leadership, Organizational Culture, and Service Quality in Higher Education: A Case Study from Indonesia - Didi Rusmidi; Abdus Salam; Ade Aspandi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Service quality in higher education has become a key indicator of institutional effectiveness, particularly for universities seeking to remain competitive and responsive to student expectations. Although instructional leadership and organizational culture are recognized as important internal determinants of service performance, their combined influence on service quality and student satisfaction in private higher education institutions remains insufficiently explored. This study examines how instructional leadership and organizational culture interact to influence service quality and student satisfaction at Universitas Sindang Kasih Majalengka, Indonesia.  This research employed a qualitative case study design to explore leadership practices and cultural dynamics within the university’s service system. Data were collected from 21 informants, including university leaders, administrative staff, and active students, through in-depth interviews, participatory observation, and document analysis. Data analysis followed the Miles and Huberman interactive model involving data reduction, data display, and conclusion drawing. Trustworthiness was ensured through triangulation and member checking. The findings indicate that instructional leadership provides clearer task direction, strengthens employee discipline, and promotes more consistent workflow management. In parallel, a collaborative and open organizational culture improves interdepartmental coordination, enhances communication, and supports collective problem-solving in administrative services. The interaction between leadership guidance and cultural support increases service responsiveness, reduces procedural delays, and positively shapes students’ perceptions of service quality. The study proposes an Instructional–Culture Service Model in which leadership functions as a structural driver while organizational culture sustains service performance. Aligning leadership practices with supportive cultural values is essential for achieving sustainable improvements in service quality and student satisfaction in higher education institutions.